Squamous cell carcinoma arising in a multiple verrucous epidermal nevus - Samira Yarak; Taila Yuri Siqueira Machado; Marilia Marufuji Ogawa; Mirian Luzia da Silva Almeida; Milvia Maria Simões e Silva Enokihara; Adriana Maria Porro (Sociedade Brasileira de Dermatologia, 2016)
Abstract Verrucous epidermal nevi are hamartomatous lesions of the epidermis that, unlike other epidermal nevi (such as sebaceous nevus or nevus comedonicus), are rarely associated with malignant neoplasms. The majority of squamous cell carcinoma develop in linear or multiple epidermal nevus and rarely in solitary epidermal nevus. In general, the prognosis is favorable. We report a case of well-differentiated invasive squamous cell carcinoma arising from a multiple verrucous epidermal nevus. Although there is no consensus on prophylactic removal of epidermal nevus, its removal and biopsy should be considered if changes occur.